Effects of temporal, spatial, and environmental factors on ciliates community in northeastern South China Sea, with notes on co-occurrence patterns of environment, phytoplankton, and ciliate - Weiwei Liu; Zijun Cheng; Shaowei Wen; Gang Li; Zhixin Ke; Daning Li; Yehui Tan (Microbiology Spectrum)
ABSTRACT Little is known about temp-spatial variations and determining mechanism of microplankton community from continental shelf to deep basin. Here, the distribution and determinants of ciliates in the northeastern South China Sea were investigated in summer and winter. We found that the alpha diversity were generally similar, but community composition showed clear difference in summer and winter. For spatial dimension, the alpha diversity significantly decreased from neritic water to deep, and the variations of community composition were only detected between upper and deep water. The determinants of community varied depending on the research scale. For entire community, the variations were higher explained by environmental factors than by temp-spatial factors. Specially, physical factors were the main determinants, which may attribute to the effects of physical processes occurred in the research area. For the three spatial subareas, season showed more significant influences on communities than other factors. Network analyses revealed that the ciliate exhibited more relationships with phytoplankton than with environment factors. Diatom and physical factors accounted for most of the ciliate-phytoplankton-environment co-occurrence relationships, suggesting their significant influences to the community stability of the microbial food web. This study improves our understanding for the mechanisms of community structuring of microzooplankton in the open sea across both space and time.IMPORTANCECiliates are important components of microplanktons and play a crucial role in global nutrient cycling. There is still large knowledge gap on their structuring mechanisms from continental shelf to deep basin. We revealed the distribution patterns of ciliate community in neSCS and assessed the relative contribution of temporal, spatial, and environmental factors for their community structuring. Compared with temp-spatial factors, environmental factors take more responsibilities for the ciliate distribution. Among the environmental factors, physical factors showed the largest contribution to community variation. Moreover, the ciliate-environment co-occurrence pattern showed that physical factors contributed more for their relationships. These findings suggested that the physical processes play key roles in temp-spatial dynamics of ciliate community in open ocean.